2022
DOI: 10.22342/jme.v13i3.pp531-548
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian students’ perceptions towards AI-based learning in mathematics

Abstract: The pandemic has indeed provided students and teachers worldwide with the experience of technology-infused teaching. Even though the pandemic is almost over, the utilization of technology in mathematics education is still needed and inseparable. Relying on cross-sectional design and phenomenological approach, this research investigates senior high school students' perceptions towards AI-based learning, particularly about their understanding and suggestions towards AI-based learning in mathematics in the contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
3
0
1
Order By: Relevance
“…A survey conducted in Indonesia showed that most students were enthusiastic and pleased with the new open limited face-to-face learning policy because students can better understand the material when they communicate face-to-face rather than through chat (Soesanto & Dirgantoro, 2021). Even before teachers integrate technology into classroom discussions, being away while discussing a lesson via a virtual environment is radically different from being present physically.…”
Section: Teaching Mathematics In Different Modalitiesmentioning
confidence: 99%
“…A survey conducted in Indonesia showed that most students were enthusiastic and pleased with the new open limited face-to-face learning policy because students can better understand the material when they communicate face-to-face rather than through chat (Soesanto & Dirgantoro, 2021). Even before teachers integrate technology into classroom discussions, being away while discussing a lesson via a virtual environment is radically different from being present physically.…”
Section: Teaching Mathematics In Different Modalitiesmentioning
confidence: 99%
“…Persepsi positif dari para peserta mengenai efektivitas AI dan teknologi pendidikan sejalan dengan penelitian sebelumnya (Salas-Pilco et al, 2022;Soesanto et al, 2022). Analisis korelasi mendukung persepsi ini, menunjukkan hubungan positif yang kuat antara frekuensi penggunaan teknologi dan efektivitas yang dirasakan (Conati & Lallé, 2023).…”
Section: Pembahasan Persepsi Positif Dan Efektivitasunclassified
“…The Indonesian government had a discussion for schools to offer required choices for the adoption of LFtFL (limited face-to-face learning) by considering diverse perspectives of PEL, as detailed in the research context. As a result, the learning shift becomes news, eliciting a range of reactions, particularly among students (Soesanto and Dirgantoro, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%